Investigation of laser cutting parameters on surface quality of stainless steel - Anuar, Azman (2010)
In this thesis, the optimal CO2 laser cutting parameters on stainless steel AISI 304 with 2 mm in thickness were studied. The cut quality to achieve a uniform kerf with minimum kerf width for circular cuts of stainless steel sheets depends on appropriate selection of process parameters was investigated. The cutting parameters considered include laser output power level, cutting speed, cutting gas pressure, and focus length. The effect of the cutting parameters on the cut quality was further investigated by monitoring the kerf width, roundness, and diameter accuracy. The experiments were conducted by using the nitrogen gas assisted laser cutting, and the factorial analysis is employed to formulate an empirical formula for optimum.